Sodium diffusion barrier coatings prepared by sol–gel method - Nocuń, Marek; Burcon, Dorota; Siwulski, Stanisław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In the case of electrically conducting layers prepared on a glass substrate, sodium diffuses into the SnO2 film and deteriorates their electric properties. Sodium barrier diffusion properties of thin layers based on SiO2, and SiO2 modified by various contents of Al2O3, TiO2, ZrO2, CeO2, prepared by sol–gel, have been the subject of this study. Morphology and optical properties of the coatings have been analyzed. XPS technique has been used to evaluate the barrier properties of prepared coatings by measuring sodium 1s peak changes after thermal treatment of the coating. The best properties have been obtained for the coating based on SiO2–Al2O3 system and containing 0.08 mol of Al. It has been found that blocking properties of the coating are mainly connected with its microstructure. The role of added modifiers lies in changing the microstructure of formed gel.
Optica Applicata, Vol. 38, 2008, nr 1, s. 171-179
Keywords: optyka; sol-gel; barrier coatings; X-ray photoelectron spectroscopy (XPS); sodium diffusion